Factors Influencing Accounting Students' Interest in Continuing Masters of Accounting Education (Study on Students of the Accounting Study Program, Faculty of Economics and Business, Universitas Jambi) - Ulfa Nurafrilliyah; Enggar Diah Puspa Arum; Reni Yustien (Indonesian Journal of Advanced Research, 2023)
This study aims to determine the effect of motivation, educational costs, length of education, and peer environment on the interest of accounting students to continue their Masters in Accounting. The sample of this study was 107 Accounting students at the Faculty of Economics and Business, Jambi University, using a probability sampling technique. Data collection was carried out by distributing questionnaires. The data analysis method used is Partial Least Square (PLS) using SmartPLS 3.0 software. The results showed that motivation, educational costs, and peer environment had a significant positive effect on students' interest in continuing their Masters in Accounting Education. Meanwhile, the length of education has no effect on students' interest in continuing their education with a master's degree in accounting.